2017
DOI: 10.3389/fimmu.2017.01535
|View full text |Cite
|
Sign up to set email alerts
|

The Human-Associated Archaeon Methanosphaera stadtmanae Is Recognized through Its RNA and Induces TLR8-Dependent NLRP3 Inflammasome Activation

Abstract: The archaeon Methanosphaera stadtmanae is a member of the gut microbiota; yet, the molecular cross-talk between archaea and the human immune system and its potential contribution to inflammatory diseases has not been evaluated. Although archaea are as bacteria prokaryotes, they form a distinct domain having unique features such as different cell wall structures and membrane lipids. So far, no microbe-associated molecular patterns of archaea which activate innate immune receptors have been identified. By stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(92 citation statements)
references
References 62 publications
1
86
1
4
Order By: Relevance
“…Although there is ample knowledge about the function of PRRs and their respective bacterial ligands, the molecular mechanism of how archaea, and specifically M. stadtmanae , are detected remained elusive. We could recently demonstrate that M. stadtmanae is recognized through its RNA by TLR8, and to a lesser extent by TLR7 (Figure ) . Phagocytosis and lysosomal acidification are necessary for the access of TLR7 and TLR8 to archaeal RNA.…”
Section: Role Of Rna‐sensing Tlrs In Detection Of Viruses Bacteria mentioning
confidence: 96%
See 3 more Smart Citations
“…Although there is ample knowledge about the function of PRRs and their respective bacterial ligands, the molecular mechanism of how archaea, and specifically M. stadtmanae , are detected remained elusive. We could recently demonstrate that M. stadtmanae is recognized through its RNA by TLR8, and to a lesser extent by TLR7 (Figure ) . Phagocytosis and lysosomal acidification are necessary for the access of TLR7 and TLR8 to archaeal RNA.…”
Section: Role Of Rna‐sensing Tlrs In Detection Of Viruses Bacteria mentioning
confidence: 96%
“…The efficacy of TLR7/8 ligands as potent adjuvants was already confirmed in different experimental setups including nonhuman primates . Interestingly, the archaeon M. stadtmanae is recognized by the innate immune system solely dependent on TLR8 and TLR7 and apparently without the involvement of any other innate immune receptors . Given the fact that to this day no pathogenic archaeon has been identified and that archaeal lipids have already been shown to hold adjuvant activity, the usage of archaea, such as M. stadtmanae , to target TLR8 in vaccine development could be considered.…”
Section: Role Of Microbial Rna In Vaccine Developmentmentioning
confidence: 97%
See 2 more Smart Citations
“…The study of Lemoinne and colleagues showed for the first time that a fungus— Exophiala— is associated with bacterial dysbiosis in PSC and leverages the findings of formerly bacterial‐only to a trans‐kingdom dysbiosis in PSC . Recently it was highlighted that previous investigations of human‐associated archaea offered a rather biased picture of archaeal diversity and new approaches for investigating this kingdom were proposed, rendering archaea with its potential immunologic implication amenable to analysis in disease context.…”
mentioning
confidence: 99%